The Effectiveness of Digital Media for Students’ Writing Abilities: A Literature Review - Fidian, Athia (Universitas Muhammadiyah Magelang, 2020)
Writing is one of the skills difficult for students to achieve and requires the right media in the process of transferring the knowledge. Learning in today's era demands learning media that supports and bridges the learning process so that it is easier conveying to students. The use of digital media based on to the students’ needs is one solution to problems related to students' writing skills. This study aims to determine the effectiveness of digital media for students' writing abilities. It conducted a literature review with two steps; database search and thematic analysis. The results of this study indicate that learning using digital media for students' writing ability is very effective in use. Furthermore, this study suggests the use of digital media to suit the specific writing skills.